2022
DOI: 10.1177/01614681221096798
|View full text |Cite
|
Sign up to set email alerts
|

Letters to My Sisters: Advice From Black Women Alumnae About How to Thrive and Survive in College

Abstract: The college success of Black women has often been narrowly defined by outcome data and does not consider some of the challenges they experience that are often racialized and gendered. Despite the increase in the number of Black women attending and graduating from college, few authors have highlighted the unique strategies that help facilitate their success. What remains unclear is how Black women define college success for themselves and what is necessary for them to thrive and survive in higher education. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Additionally, scholars suggest that Black college women build joyful and life-sustaining friendships that increase their understanding of history, self, and community (Alexander & Bodenhorn, 2015; S. Davis, 2018; Hughes, & Heuman, 2006; Reavis et al, 2022). Leath, Mims, et al (2022) found that within their friendships with other Black women at PWIs, Black women processed their experiences of discrimination, built social and professional networks with Black women who had similar interests, and moved toward affirmative understandings of their intersectional identities.…”
Section: Charting Black Women’s Freedom At Pwis Through Black Feminis...mentioning
confidence: 99%
“…Additionally, scholars suggest that Black college women build joyful and life-sustaining friendships that increase their understanding of history, self, and community (Alexander & Bodenhorn, 2015; S. Davis, 2018; Hughes, & Heuman, 2006; Reavis et al, 2022). Leath, Mims, et al (2022) found that within their friendships with other Black women at PWIs, Black women processed their experiences of discrimination, built social and professional networks with Black women who had similar interests, and moved toward affirmative understandings of their intersectional identities.…”
Section: Charting Black Women’s Freedom At Pwis Through Black Feminis...mentioning
confidence: 99%